Might the COVID-19 pandemic spur increased murder-suicide?. Issue 3 (23rd June 2020) - Joiner, Thomas E.; Lieberman, Amy; Stanley, Ian H.; Reger, Mark A.
Abstract : Purpose: The coronavirus 2019 (COVID-19) pandemic has prompted concerns about an increased risk for psychological distress, broadly and suicide mortality, specifically; it is, as yet, unclear if these concerns will be realized, but they are plausible. Design/methodology/approach: The authors demonstrate why researchers, clinicians, policymakers and other public health stakeholders should be vigilant to the potential increases in murder-suicide in the wake of the COVID-19 pandemic. Findings: During the COVID-19 pandemic, there have been reports of increased gun sales, alcohol sales, intimate partner violence and child neglect/abuse. These factors give one serious pause regarding the potential for murder-suicide, especially in the context of other pandemic-related stressors (e.g. loneliness, economic stress, health anxiety). Originality/value: This paper highlights pandemic-related factors that might spur increased murder-suicide and encourages murder-suicide prevention efforts to take place alongside other pandemic-related public health interventions.